2017
DOI: 10.1371/journal.pbio.2001246
|View full text |Cite|
|
Sign up to set email alerts
|

Early postnatal exposure to isoflurane causes cognitive deficits and disrupts development of newborn hippocampal neurons via activation of the mTOR pathway

Abstract: Clinical and preclinical studies indicate that early postnatal exposure to anesthetics can lead to lasting deficits in learning and other cognitive processes. The mechanism underlying this phenomenon has not been clarified and there is no treatment currently available. Recent evidence suggests that anesthetics might cause persistent deficits in cognitive function by disrupting key events in brain development. The hippocampus, a brain region that is critical for learning and memory, contains a large number of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 60 publications
3
69
3
Order By: Relevance
“…Taken together, these data indicate that isoflurane interferes with the formation of excitatory synapses in developing cultured neocortical neurons and that this effect may be due to actions on the mTOR pathway. Our own work in vivo shows that newborn dentate gyrus neurons in mice exposed to GA with isoflurane are found to have reduced numbers of spines overall and profoundly reduced numbers of mushroom morphology spines over a month later [8]. As in our culture model, we found that this effect was reversible by treatment with rapamycin not acutely, but for a week after the exposure.…”
Section: Effects Of 18% Isoflurane Exposure For 6hrs On Synaptogenesissupporting
confidence: 59%
See 1 more Smart Citation
“…Taken together, these data indicate that isoflurane interferes with the formation of excitatory synapses in developing cultured neocortical neurons and that this effect may be due to actions on the mTOR pathway. Our own work in vivo shows that newborn dentate gyrus neurons in mice exposed to GA with isoflurane are found to have reduced numbers of spines overall and profoundly reduced numbers of mushroom morphology spines over a month later [8]. As in our culture model, we found that this effect was reversible by treatment with rapamycin not acutely, but for a week after the exposure.…”
Section: Effects Of 18% Isoflurane Exposure For 6hrs On Synaptogenesissupporting
confidence: 59%
“…Numerous studies have found that early postnatal exposure to GA in rodents results in deficits in performance on tests of learning and memory [7][8][9][10][11][12][13][14][15], but rodent anesthesia models introduce a confound of physiologic perturbation that is hard to measure and also the short timeline of rodent brain development might exaggerate the consequences of a toxic developmental exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a previous animal study with propofol (23), we found Sevo lengthy anesthesia induced an increase of dendritic spines and synapses at P21 in the cortex, but decreases were also reported (24, 25). We did not observe significant astrocyte nor neuron structural deficits in developing hippocampal CA1sr and DG-mo regions, whereas a few studies found abnormal synaptic growth (26), altered synaptic plasticity (24) in the hippocampus. The inconsistency may due to different anesthetic agents (isoflurane, sevoflurane, propofol etc.)…”
Section: Discussioncontrasting
confidence: 91%
“…For apical dendrites, the 70 μm long segment was also analyzed every 10 μm of dendritic length. For spine classification, the Filament function of Imaris was used; stubby: length (spine) < 1.5 and max width (head) < mean width (neck) ×1.2; mushroom: max width (head) > mean width (neck) × 1.2 and max width (head) > 0.3; the rest were defined as long-thin (26). We only quantified the total and mushroom spine density, but the stubby and long thin were difficult to be classified in many cases due to the limited image resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the mTOR pathway was found to take part in the regulation of dendritic growth, synapse formation, and synaptic protein expression [85][86][87]. It was reported that general anesthetics, including sevoflurane, induced developmental neuronal injury by activating the mTOR pathway [87][88][89][90]. In light of the fact that mTOR and BDNF interact in a complicated way in physiological or pathological settings [91,92], we did not explore the crosstalk between BDNF and mTOR signaling in the sevoflurane-induced injury in the present study.…”
mentioning
confidence: 99%